2001
DOI: 10.1021/jp012278z
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic Pairing in Polyaniline Salt−Zeolite Nanocomposites

Abstract: Polyaniline (PANI) zeolite composites have been prepared by oxidative polymerization of anilinein the presence of zeolite 13X, producing composite materials with PANI/zeolite weight ratios from about 0.5 to 55. The DC conductivity of the composite materials decreased exponentially with zeolite weight fraction. Pure PANI was paramagnetic while the PANI/zeolite complexes with weight ratios larger than 20 showed an appreciable antiferromagnetic component as indicated by temperature dependence of their electron sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…The diameter of the P/Z composite was between 300 and 600 nm, which may be due to the accumulation of single PANI chains released from the zeolite layers (Fig. 3c); it has been reported that one zeolite layer contains many PANI chains [28,32].…”
Section: Characterization Studiesmentioning
confidence: 91%
“…The diameter of the P/Z composite was between 300 and 600 nm, which may be due to the accumulation of single PANI chains released from the zeolite layers (Fig. 3c); it has been reported that one zeolite layer contains many PANI chains [28,32].…”
Section: Characterization Studiesmentioning
confidence: 91%
“…The time lag between each measurement and the next one on the same sample was 5 min. The room‐temperature dc conductivity of pure PANI ([H + ] = 1 M ) is 1.20 S/cm, as measured by a four‐point probe technique 2…”
Section: Methodsmentioning
confidence: 99%
“…As an electrically conductive polymer, polyaniline (PANI) has attracted considerable interest for several decades. Tremendous research has been done to improve the conductivity and processability of PANI by forming interpenetrating polymer networks (IPNs), copolymers, composites, and blends 1–8. This report concerns the synthesis and characterization of PANI/crosslinked polyvinylacetate (PVAc) semi‐IPNs.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous conducting polymer nanocomposites have also gained increased attention over the last decade . These materials exhibit special mechanical , electronic , optical , and magnetic properties .…”
Section: Introductionmentioning
confidence: 99%